Biodegradable Nanocarriers Resembling Extracellular Vesicles Deliver Genetic Material with the Highest Efficiency to Various Cell Types. Issue 3 (16th December 2019) - Tarakanchikova, Yana; Alzubi, Jamal; Pennucci, Valentina; Follo, Marie; Kochergin, Boris; Muslimov, Albert; Skovorodkin, Ilya; Vainio, Seppo; Antipina, Maria N.; Atkin, Vsevolod; Popov, Alexey; Meglinski, Igor; et al.
Abstract: Efficient delivery of genetic material to primary cells remains challenging. Here, efficient transfer of genetic material is presented using synthetic biodegradable nanocarriers, resembling extracellular vesicles in their biomechanical properties. This is based on two main technological achievements: generation of soft biodegradable polyelectrolyte capsules in nanosize and efficient application of the nanocapsules for co‐transfer of different RNAs to tumor cell lines and primary cells, including hematopoietic progenitor cells and primary T cells. Near to 100% efficiency is reached using only 2.5 × 10 −4 pmol of siRNA, and 1 × 10 −3 nmol of mRNA per cell, which is several magnitude orders below the amounts reported for any of methods published so far. The data show that biodegradable nanocapsules represent a universal and highly efficient biomimetic platform for the transfer of genetic material with the utmost potential to revolutionize gene transfer technology in vitro and in vivo. Abstract : This work demonstrates a new tool for the transfer of genetic material. The developed biodegradable polyelectrolyte nanocapsules exhibit high levels of uptake and transfer to various cell types, including hematopoietic stem cells. A co‐transfer and regulated release of several types of RNAs or DNAs are possible using this approach, and are able to revolutionize gene transfer technology.